Nível de institucionalização e impacto da gestão financeira no desempenho das micro e pequenas empresas - Meirelles, Marco Aurélio Scartezini Soares de (2018)
Micro and Small Enterprises (MSE) play an important role in the economic and social development of nations: they produce innovation, generate wealth and jobs. However, understanding the dynamics of this universe has proved to be a major challenge for academic studies. This paper aims to test if the short-term finance theory is an institutionalized practice in MSE and financial factors influence the performance of these companies. From the methodological point of view, the present study has a quantitative approach, descriptive and explanatory objective, field survey (survey) in its procedure and crosscutting in its temporal dimension. The sample consisted of 109 companies associated to the Commercial and Industrial Association of Guarapuava (ACIG). As a data collection instrument, a structured questionnaire was used, distributed and answered electronically (online). Among the main evidences found, most of the companies are from the Trade and Services Sector (69.7%), of which 93.6% have up to 30 employees. The predominant school education of the respondents is at postgraduate level (47.7%), with 51.4% of the respondents being the founders or main partners and 78% of these companies have been in existence for more than 8 years. In terms of performance, 77.8% said that they had profit margins above 10% in the last year, 45.8% indicated that they had an increase in turnover and the workforce remained stable. In relation to the central objectives of the study, it was verified that there is institutionalization of financial practices, and that this institutionalization is denser at the levels of objectification and sedimentation. In terms of the impact of the financial factors on the performance of these companies, the age of the company, billing, the form of payment of purchases and the level of institutionalization of financial practices were influential. The regressor model presented r² of 26%, with turnover being the most influential variable. Among the theoretical contributions observed in the study it is highlighted the fact that the institutionalization of short-term financial practices provides a gain in performance. From a practical perspective, the study offers operational and strategic alternatives that can constitute actions and policies aimed at the development of Micro and Small Companies.